Mass customization under the internet of things - Aziz shnawa, Wissam (Opción, 2020)
The study aims to investigate mass customization under the internet of things via comparative qualitative research methods. As a result, manufacturing, supplychain, and logistics functions will benefit from the broad penetration of digital sensors and smart tags that will offer greater potential for visibility, flexibility, and control of product flows, as well as for automation of tasks that enhance product value. In conclusion, the adoption of Mass Customization on the Internet of Things lead to better control and reduce costs and achieve the efficiency of production and this leads to achieving customer satisfaction.